Macierzyństwo pod medycznym nadzorem. Wybrane aspekty medykalizacji macierzyństwa - Mazurek, Emilia (Kultura-Społeczeństwo-Edukacja, 2014)
The growing importance of medicine as a science, but also as a certain ideology, caused the medical supervision of different spheres of human life, not just those related to human health and the organism. Using the authority of medicine and its representants, medical discourse (re)constructs the meaning of motherhood, uses its own conceptual categories to describe the experience of performing the role of the mother, imposes their own interpretations of processes and problems inherent in this experience. In relation to the concept of Peter Conrad, author presents the selected practices of medicalization of motherhood and their possible consequences. In addition, the mother is shown as a person who learns in the context of experienced medicalization practices.